2021
DOI: 10.1038/s41598-021-88218-3
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Catechin and curcumin interact with S protein of SARS-CoV2 and ACE2 of human cell membrane: insights from computational studies

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A molecular docking study of 18 plant constituents to SARS-CoV-2 proteins showed that EGCG bound with higher affinity than the antiviral drugs chloroquine and remdesivir to all tested SARS-CoV-2 protein targets, including Mpro, S protein, S2 subunit of the S protein, RBD-ACE2 complex and NSP15 endoribonuclease [ 67 ]. The previous study was in agreement with another molecular docking study which showed high binding affinity of EGCG and catechin to SARS-CoV-2 proteins such as Mpro, RNA-dependent RNA polymerase, PLpro, RBD of S protein, NSP6, N protein, ACE2 receptor and ACE2 receptor bound to RBD [ 68 , 69 , 70 , 71 ]. The binding of EGCG to SARS-CoV-2-S protein was further confirmed by a molecular docking study which showed high-affinity binding to S protein [ 72 ], and another study which showed high-affinity binding not only to the S protein of the wild-type strain but to the UK mutant strain S protein [ 73 ].…”
Section: Anti-sars-cov-2 Activity Of Catechinssupporting
confidence: 89%
“…A molecular docking study of 18 plant constituents to SARS-CoV-2 proteins showed that EGCG bound with higher affinity than the antiviral drugs chloroquine and remdesivir to all tested SARS-CoV-2 protein targets, including Mpro, S protein, S2 subunit of the S protein, RBD-ACE2 complex and NSP15 endoribonuclease [ 67 ]. The previous study was in agreement with another molecular docking study which showed high binding affinity of EGCG and catechin to SARS-CoV-2 proteins such as Mpro, RNA-dependent RNA polymerase, PLpro, RBD of S protein, NSP6, N protein, ACE2 receptor and ACE2 receptor bound to RBD [ 68 , 69 , 70 , 71 ]. The binding of EGCG to SARS-CoV-2-S protein was further confirmed by a molecular docking study which showed high-affinity binding to S protein [ 72 ], and another study which showed high-affinity binding not only to the S protein of the wild-type strain but to the UK mutant strain S protein [ 73 ].…”
Section: Anti-sars-cov-2 Activity Of Catechinssupporting
confidence: 89%
“…Curcumin derived from the rhizome of turmeric (Curcuma longa) has high binding affinity for SARS-CoV-2 spike protein, host cell ACE2 receptor, and RBD/ACE2 complex [99], suggesting that curcumin may inhibit the cellular entry of SARS-CoV-2. Curcumin also shows virucidal effects independently of SARS-CoV-2 variants and inhibitory effects on the release of pro-inflammatory cytokine IL-1b, IL-6, and IL-8 [100].…”
Section: Treatment With Curcumin and Outcomementioning
confidence: 99%
“…Human pathogenic coronavirus, including severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2, it binds to the angiotensinogen-converting enzyme 2 (ACE2), a recently discovered mono-carboxypeptidase and the first ACE homolog, and then enters the cell ( 1 ). SARS-CoV S1 contains a receptor-binding domain (RBD) that explicitly recognizes ACE2 as its receptor ( 2 ), and tea polyphenols (TPs) have been found to bind to RBD to inhibit virus invasion ( 3 ). Numerous studies have demonstrated TPs to prevent obesity, diabetes, cardiovascular disease, cancer, and antiviral activity and fight diseases caused by oxidative stress and inflammation ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%